Silver clusters templated by homo- and hetero-anions. Issue 22 (19th May 2020) - Pan, Zhong-Hua; Deng, Cheng-Long; Wang, Zhi; Lin, Jin-Qing; Luo, Geng-Geng; Sun, Di
Abstract : This article highlights the use of homo- and hetero-anion templates for the ordered assembly of high-nuclearity silver clusters. Abstract : Silver clusters with atomic precision have garnered immense attention owing to their aesthetic structures and fascinating properties. Assembly of silver clusters involves organizing positively charged silver ions into an intricate entity in an ordered fashion. To this end, the established effective route to assemble well-ordered silver clusters uses facile template anions as structure-directing agents. The past decades have witnessed a single anion template strategy widely used to construct silver clusters. In order to overcome the nuclearity limitation from the single anion template, multiple anionic templates have been recently introduced into the controllable preparation of high-nuclearity silver clusters. In this highlight, we will summarize the recent advances in homo- and hetero-anion templated silver clusters, in which their synthetic methods, crystal structures and anionic template directing effects as well as properties will be discussed.